Evaluation of TAERO UGV structural collision resistance using FEM analysis - Nowakowski, Marek; Kosiuczenko, Krzysztof (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The increasing adoption of unmanned platforms in sectors such as defense, agriculture, and logistics highlights critical challenges, including traversal capability and collision resistance in unstructured terrain. This study investigates the crashworthiness of the developed TAERO UGV using finite element method (FEM) analysis. The structural components critical to collision energy absorption were identified and analyzed. Descriptions of the LS-DYNA simulation model, material properties, and boundary conditions are provided. The primary objective was to numerically assess the bumper performance during impact, considering the operational speeds and crumple zone of the vehicle. An optimized numerical model was introduced to efficiently simulate vehicle collisions, focusing on key structural elements. Various scenarios were simulated to examine deformation, stress distribution, and bumper behaviour. Presented numerical analysis indicates that impacts with typical obstacles, like tree trunks in unstructured terrain, cause minimal damage, not affecting the operational vehicle capability. Minor bumper damage, such as dents, vary and are more noticeable at higher speeds, while almost imperceptible up to 25 km/h. Stress distribution highlights the role of side components in energy absorption and structural deformation. The results confirm the structural integrity of the vehicle and provide valuable data on its operation performance in complex environments during specialized missions.